Framework for component-based software engineering of embedded software in resource constrained real-time systems - Abg. Jawawi, Dayang Norhayati (Faculty of Computer Science and Information System, 2008)
Applying component-based software engineering (CBSE) to embedded realtime (ERT) systems poses significant challenges to industrial software processes due to the resource-constrained and real-time requirements of the systems. In this research, a framework for Component-Oriented Programming (COP) of ERT software has been developed to enable a systematic development through CBSE. To show the flexibility of the COP framework, two component-based development (CBD) approaches were proposed. The first CBD approach called ELCRA was proposed to facilitate a systematic CBSE for early life-cycle reuse of ERT systems. The second approach using MARMOT method was developed to support multiconstraint ERT software requirement and multi-disciplinary knowledge of the domain. The results of implementing the framework and approaches in developing software for real ERT systems showed that they can fulfill the ERT requirements especially the resource constraint requirement. The amount of reuse measurement results showed up to 80% of reuse rate were achieved on the two ERT case-studies tested. The case-studies implementation results and software reuse measurements indicate that the developed framework promotes systematic development of component-based ERT software and component-based reuse qualities.